1978
DOI: 10.1083/jcb.78.3.919
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of the membrane envelope enclosing the bacteroids in soybean root nodules.

Abstract: The membrane envelope enclosing the bacteroids in soybean root nodules is shown by ultrastructural and biochemical studies to be derived from, and to retain the characteristics of, the host cell plasma membrane. During the early stages of the infection process, which occurs through an invagination, Rhizobium becomes surrounded by the host cell wall and plasma membrane, forming the infection thread. The cell wall of the infection thread is degraded by cellulolytic enzyme(s), leaving behind the enclosed plasma m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
53
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(55 citation statements)
references
References 38 publications
2
53
0
Order By: Relevance
“…It has also been reported that the isolated peribacteroid membrane contains an ATPase (Robertson et al, 1978;Verma et al, 1978;Bassarab et al, 1986;Domigan et al, 1988). The latter enzyme was also demonstrated in intact soybean symbiosomes (bacteroids enclosed by the peribacteroid membrane) (Udvardi and Day, 1989; Ou Yang et al, 1990;Udvardi et al, 1991).…”
mentioning
confidence: 77%
“…It has also been reported that the isolated peribacteroid membrane contains an ATPase (Robertson et al, 1978;Verma et al, 1978;Bassarab et al, 1986;Domigan et al, 1988). The latter enzyme was also demonstrated in intact soybean symbiosomes (bacteroids enclosed by the peribacteroid membrane) (Udvardi and Day, 1989; Ou Yang et al, 1990;Udvardi et al, 1991).…”
mentioning
confidence: 77%
“…l h e need to produce enormous amounts of membrane to enclose bacteria provides a model system for membrane biogenesis in plants. This membrane proliferation amplifies the basic machinery 20 to 30 times over that in a normal root cell (Verma et al, 1978;Verma and Fortin, 1989 Cocking, 1972), but such entry does not ensure that the bacteria will survive and multiply, and the invasive bacteria often kill the plant cells. Death of the plant cell could be a hypersensitive reaction to the invader.…”
Section: Future Directionsmentioning
confidence: 99%
“…to detect general phosphatase activity (see Woods & ATPase activity associated with plant membranes Gay, 1987), or use of the plasma membrane H^-has been studied biochemically using isolated mem-ATPase inhibitors diethylstilbestrol (DFS) (Marx et brane preparations (including vesicles) and by cyto-al, 1982) and sodium orthovanadate (Gianinazzichemical localization in electron micrographs (e.g. Pearson & Gianinazzi, 1988).…”
mentioning
confidence: 99%